2015
DOI: 10.1096/fj.15-279554
|View full text |Cite
|
Sign up to set email alerts
|

Studying both sexes: a guiding principle for biomedicine

Abstract: In May 2014, the U.S. National Institutes of Health (NIH) announced that it will ensure that investigators account for sex as a biological variable (SABV) in NIHfunded preclinical research as part of the agency's rigor and transparency initiative. Herein, I describe in more detail the rationale behind the SABV policy component and provide additional detail about policy goals. In short, studying both sexes is a guiding principle in biomedical research that will expand knowledge toward turning discovery into he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
215
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(229 citation statements)
references
References 44 publications
2
215
0
Order By: Relevance
“…1 In Ophthalmology there are notable sex differences in many traits and diseases, but very little is known about root causes to enable design and implementation of diagnostic, preventive and treatment strategies. 2 Dry eye disease (DED) is no exception, as numerous epidemiological studies have shown that DED is far more prevalent in women than in men and biological studies have shown that sex has a major influence on the regulation of the ocular surface and adnexa.…”
Section: Introductionmentioning
confidence: 99%
“…1 In Ophthalmology there are notable sex differences in many traits and diseases, but very little is known about root causes to enable design and implementation of diagnostic, preventive and treatment strategies. 2 Dry eye disease (DED) is no exception, as numerous epidemiological studies have shown that DED is far more prevalent in women than in men and biological studies have shown that sex has a major influence on the regulation of the ocular surface and adnexa.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we offer an approach to thinking about variation in brain structure and function that pulls us outside the dimorphism-difference formulation. We consider the implications of this approach for future research including both basic and clinical inquiry and in the light of the requirement that sex be explicitly included in all research studies by the United States National Institutes of Health [25,26] and of similar policies by Canada and the European Union [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons put forward for the preferential use of males include increased variability attributable to fluctuating gonadal hormone levels throughout the estrous cycle and sample size implications of planning sexbased analyses. 2,3 Evidence to support these concerns is limited for most experimental settings, however. [3][4][5] Our review of preclinical research published in leading cardiovascular journals over the past 10 years demonstrates that sex bias is prevalent and increasing, contrasting with advances made in clinical research designs and reporting.…”
mentioning
confidence: 99%